THÀNH PHẦN LOÀI CÁ CỬA SÔNG HỒNG, KHU BẢO TỒN THIÊN NHIÊN TIỀN HẢI, THÁI BÌNH - Dực, Nguyễn Hữu (Nhà xuất bản Nông nghiệp, 2016)
Results of the survey conducted from 25 to 28 June, 2006 show that the total number of fish species at the Red River Estuary (the part located in Tien Hai Natural Reserve, Thai Binh Province) was counted at 186, with 104 genera and 54 families of 15 different orders. The most dominant composition was the perciformes order. Among the species, five are listed in the 2007 Vietnam Red Data Book. They are Bostrichthys nasussis sinensis (Lacepede) - level CR; Clupanodon thrissa (Linnaeus) - level EN; Nematolosa nasus (Bloch), Elops saurus (Linnaeus) and Konosirus punctatus (Temminck & Schlegel) level VU. About 43.1% of them (81 species) have economic values. Among these, Clupeidae, Cynoglossidae, Gobiidae, Sparidae and Geridae are of high economic values. The rest of them are small fish but they are of economic importance to the local people.